The Correlation Between Students' Listening Anxiety and Listening Achievement at a University - Salsabila Fitriah Ramadhani; Jamiluddin Jamiluddin; Maghfira Maghfira; Aminah Suriaman (Universitas Pahlawan Tuanku Tambusai, 2026)
Listening is an essential skill in English as a Foreign Language (EFL) learning; however, many students experience listening anxiety that may affect their academic performance. Previous studies have reported inconsistent findings regarding the correlation between listening anxiety and listening achievement, indicating the need for further investigation in different educational contexts, particularly in Indonesian higher education. This study aimed to examine the correlation between students' listening anxiety and listening achievement among fourth-semester students of the English Education Study Program at Tadulako University. A quantitative correlational design involving 35 students was employed. Data were collected using a validated listening anxiety questionnaire and students' final listening examination scores and analyzed using the Pearson Product-Moment Correlation test. The findings revealed a very weak negative correlation between listening anxiety and listening achievement (r = −0.063, p = .720), indicating no statistically significant relationship between the two variables. The study concludes that listening anxiety was not a determining factor of students' listening achievement in this context. These findings contribute to the growing body of EFL listening research by providing empirical evidence from an Indonesian university setting and suggest that factors beyond anxiety, such as listening strategies, language proficiency, and learner motivation, may play a more substantial role in determining listening achievement.